PENGGUNAAN PENDEKATAN NAIVE BAYES DALAM APLIKASI DIAGNOSIS PENYAKIT SERTA SYARAT HIDUP TANAMAN MELON BERBASIS WEBSITE (STUDI KASUS: DESA JATIMLEREK KECAMATAN PLANDAAN KABUPATEN JOMBANG ) - Muchammad Rizal Bahrevi; Mufarrihah, Iftitaahul; Sujatmiko, Bambang; Reza Augusta Jannatul Firdaus (Inovate, 2024)
Melon (Cucumis melo L.) is the name of a fruit plant as well as a fruit producer that belongs to theCucurbitaceae family. Many farmers try to grow melon plants but are unsuccessful due to diseases orignorance of the environment in which the melon lives. Farmers can better control melon plant infections byhaving knowledge of the different types of diseases that attack it. The success rate of disease control in melonplants can be determined by the accuracy of the method and target of the disease being controlled. NaiveBayes algorithm is a technique that will be applied in the system to identify various diseases and livingconditions of melon plants. A probability classification called Naive Bayes creates a set of possibilities bysumming the combination values and frequencies of a particular data set. In this research, a system fordiagnosing diseases and living conditions of melon plants by implementing Naive Bayes was developed.This system is built using html, php, and mysql programming languages and the use of bootstrap framework.Tests were conducted on several users to evaluate the performance, functionality, and effectiveness of thesystem. The test results show that the accuracy rate reaches 79.2%.Keywords: Implementation, Naive Bayes, Diagnosis, Melon Plant, Websites.